Core outcome sets in dermatology: report from the second meeting of the International Cochrane Skin Group Core Outcome Set Initiative. (18th April 2018) - Kottner, J.; Jacobi, L.; Hahnel, E.; Alam, M.; Balzer, K.; Beeckman, D.; Busard, C.; Chalmers, J.; Deckert, S.; Eleftheriadou, V.; Furlan, K.; Horbach, S.E.R.; et al.
Summary: Clinical trials are needed to find out whether drugs or other treatments work for people with skin diseases. People who take part in a clinical trial are often put into two groups. One group gets the test treatment and the other gets the control treatment. After the treatment has been tried over a period of time, the effect of the treatment in both groups is compared. The more the disease has improved, and the fewer the side effects, the better the treatment. It is very important to measure a person's response to treatment correctly, or else the study conclusions are useless. For instance, itch can be measured by asking the patient directly or by a doctor looking at scratch marks. Both "outcomes" give different information. It is equally important that researchers include the same outcomes when doing clinical trials in similar patient groups. In the field of atopic eczema for instance, it would be very difficult to compare the results of different treatments if one only measured skin redness, another measured itch and another measured only quality of life. You would think that by now, researchers over the world would have got together to sort our which outcomes should always be measured in certain skin diseases. But the reality is that everyone measures different things, making it almost impossible to combine the studies into something that makes sense. Now, a group of researchers, patients, and other experts are finally getting together to discuss how to best measure the treatment effects (or outcomes) in clinical trials of people with skin diseases. At an international meeting in Germany in January 2017, there was agreement about the best way to choose the "core" outcomes by looking at the best evidence and by asking lots of people. But some other things, such as how to best involve patients in making such decisions and how to reach agreement within a larger group of experts, turned out to be more tricky. The international CSG‐COUSIN group are committed to following through their work and hope to come up with a set of core outcomes that should always be measured in people with different skin diseases, so that patients, doctors, nurses and those who pay for healthcare can make better sense of the hundreds of clinical trials that are being done today. Abstract : Linked Article: Kottner et al. Br J Dermatol 2018; 178 :e279–e285